Složenost pristupa problemu organizacije zračnog prometa - Radačić, Željko (Promet - Traffic&Transportation, 2012)
The basic aspect that is the subject of interest in this paper refers to the air traffic management. If it is true that the structure of air transport makes a subsystem of air traffic also originating from the general theory of complex systems and the theory of modem management (structuring), then it appears from the theoretical and practical viewpoint possible and correct to decompose this subsystem in to a number of further subsystems of lower hierarchical level. Thus when dealing with the issue of air traffic management it is possible to discuss: the structure of air traffic authorities, the structure of air traffic as a system, the structure of transport service, the structure of passenger and freight services, internal structure of airlines, of airports, and of ATC, the structure of individual business functions and the structure of transport process.